2016
DOI: 10.1200/jco.2015.63.4048
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Multiagent Therapy, Including Dose-Compressed Cycles of Ifosfamide/Etoposide and Vincristine/Doxorubicin/Cyclophosphamide, Irinotecan, and Radiation, in Patients With High-Risk Rhabdomyosarcoma: A Report From the Children's Oncology Group

Abstract: Purpose Patients with metastatic rhabdomyosarcoma (RMS), except those younger than 10 years with embryonal RMS, have an estimated long-term event-free survival (EFS) of less than 20%. The main goal of this study was to improve outcome of patients with metastatic RMS by dose intensification with interval compression, use of the most active agents determined in phase II window studies, and use of irinotecan as a radiation sensitizer. Patients and Methods Patients with metastatic RMS received 54 weeks of therapy:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
210
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(217 citation statements)
references
References 20 publications
5
210
2
Order By: Relevance
“…Breast malignancies commonly diagnosed in children and adolescents have been reported to be metastases originating from neuroblastoma, RMS, or hematologic malignancies [23]. RMS presents mostly at around 5 years of age and in adolescence [5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast malignancies commonly diagnosed in children and adolescents have been reported to be metastases originating from neuroblastoma, RMS, or hematologic malignancies [23]. RMS presents mostly at around 5 years of age and in adolescence [5]. …”
Section: Discussionmentioning
confidence: 99%
“…The most common primary sites of RMS are the head and neck region (40%) [3], the genitourinary system (22%), the extremities (18%), the trunk, chest wall, perineum, and retroperitoneum [4,5], and the biliary tract [6]. Breast involvement is very rare, both as a primary or as a metastatic site [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although overall survival for children with RMS approaches 70%, the presence of the paired box 3-forkhead box O1 (PAX3-FOXO1) fusion strongly associates with adverse outcome predictors such as an extremity primary site and metastatic disease at diagnosis (16). Despite 30 y of clinical trials, PAX3-FOXO1 fusion-positive RMS patients with metastatic disease are considered incurable with current therapies (17). Difficulties in directly inhibiting the PAX3-FOXO1 transcription factor chimera and a largely unaltered genomic landscape in RMS have, to date, precluded precision medicine in this disease (18,19).…”
Section: Significancementioning
confidence: 99%
“…The most recent Children's Oncology Group (COG) trial for low-risk RMS showed that patients have an excellent outcome [2-year event-free survival (EFS), 88%; overall survival (OS), 98%] with short therapy duration (9). Whereas the most recent COG high-risk RMS study showed poor outcome in 3-year EFS 38% (10).…”
Section: Introductionmentioning
confidence: 99%